Education and science: current trends - Savotkin N. A., Pashkevich O. I., Alisin V. V., Litvinskiy V. M., Morev A. V., Lysenko E. M., Korotenko S. V., Mishina E. V., Kozikhina M. V., Lezina T. V., Kolotygina E. A., Nadtochii I. B., Zernii I. V., Bakhmisova M. A., Tolmacheva N. A., Kuzovova N. L., Tolstova O. S., Variushchenko V. I., Gaikova O. V. (Education and science: current trends, 2019)
the purpose of the article is to identify and substantiate the innovative pedagogical searches in the field of the use of constantly developing information and communications technologies (ICT) in Russia and China. A comparative analysis of types of teaching was carried out taking into account the active use of information and communications technologies. Chinese experience is of great interest to Russian teachers due to the rich Chinese philosophy, national traditions and pedagogical knowledge. Russia and China have deep historical, integration, economic and cultural ties. The system of Chinese education brought the country to the leading position in the world and to the second place in the economy. The author reveals similarities in the education system of Russia and China. Positive achievements in the education systems of each of these countries are mutually enriching each other, acquiring a global character. At the same time, the Chinese education system has a number of achievements that have to be integrated into the Russian education system. The study compares the traditional and innovative types of teaching in Russia and China in terms of indicators: an approach to teaching, a dominant idea, a goal, centering on the subject of activity, teacher (instructor) roles, student roles, values on which a teacher (an instructor) relies, advantages, disadvantages, main results. The study identifies the essential characteristics of the types of teaching and makes it possible to establish that, at a theoretical level, the traditional and innovative types of teaching are opposed, but in practice they organically combine, complement and reinforce each other. China's experience in the use of ICTs in education is invaluable in the implementation of the modernization of education in Russia.
Keywords: интеграция; integration; ИКТ; информационно-коммуникационные технологии; ICT; педагогическая технология; традиционный тип обучения; инновационный тип обучения; information and communications technologies; educational technology; traditional type of teaching; innovative type of teaching